Prospects And Challenges Of Emerging Technologies In Architectural Design Practice Within The Nigerian Context (Journal of Namibian Studies : History Politics Culture, 2023)
The United Nations’ Sustainable Development Goal (SDG) 9 (Industry, Innovation,` and Infrastructure) and the fast rise of technological advancements globally demand a need for Nigeria as a third-world country to keep up with this rapid progression of technology. This study examined how these technological advances are affecting Nigerian architectural design practices. It also looked at how architectural design is now practiced vis-a-vis the problems that hinder the total acceptance and use of new technology in the industry. Hence, the research utilised literature review and questionnaires to identify emerging technologies needed for Nigerian architects to be able to participate in the fast-rising global trend such as Computer Aided design (CAD), 3D modeling, Building Information Modelling (BIM), Data-driven design, Artificial Intelligence (AI) and Virtual reality amongst a few others. The literature revealed that the identified technologies have roles such as improved efficiency, conceptual modeling, and articulate visualisation to play. The findings from this research indicate that limited technological knowledge among architects ranks the highest among the challenges in adopting emerging technologies in Nigeria as identified by 72.7% of respondents. This is due to economic factors such as the high cost of procuring technological equipment as well as technical factors such as insufficient technical knowledge. Therefore, it is highly recommended that Architects in Nigeria begin to explore and integrate these technologies into their day-to-day practices so they can begin to enjoy the benefits that come with it. These benefits include efficiency, reduced error, increased innovations, and data-driven designs.